2021
DOI: 10.3390/chemosensors10010002
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Optode Array Based on Pluronic-Stabilized Microspheres for Differential Sensing

Abstract: Differential sensing techniques are becoming nowadays an attractive alternative to classical selective recognition methods due to the “fingerprinting” possibility allowing identifying various analytes without the need to fabricate highly selective binding recognition sites. This work shows for the first time that surfactant-based ion-sensitive microspheres as optodes in the microscale can be designed as cross-sensitive materials; thus, they are perfect candidates as sensing elements for differential sensing. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The microspheres selective for both anions (A) and cations (C) contained a chromoionophore (CH) as an optical transducer, which can be protonated/deprotonated in the presence of an ion exchanger (R). This change in the protonation degree of the chromoionophore is responsible for the change in the optical properties of the produced microspheres according to eqs and (for AS-MPs and CS-MPs, respectively). ,, The next two types of microspheres were incorporated with the manganese porphyrins, which played the double role of an ionophore and an optical transducer, according to eqs and . CH normalm + normalR normalm + + normalH aq + + normalA aq CHH normalm + + normalR + normalA normalm CHH normalm + + normalR normalm + normalC aq + CH normalm + normalH aq + + normalC + normalR normalm MnOEPCl normalm + normalA aq MnOEPA normalm …”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The microspheres selective for both anions (A) and cations (C) contained a chromoionophore (CH) as an optical transducer, which can be protonated/deprotonated in the presence of an ion exchanger (R). This change in the protonation degree of the chromoionophore is responsible for the change in the optical properties of the produced microspheres according to eqs and (for AS-MPs and CS-MPs, respectively). ,, The next two types of microspheres were incorporated with the manganese porphyrins, which played the double role of an ionophore and an optical transducer, according to eqs and . CH normalm + normalR normalm + + normalH aq + + normalA aq CHH normalm + + normalR + normalA normalm CHH normalm + + normalR normalm + normalC aq + CH normalm + normalH aq + + normalC + normalR normalm MnOEPCl normalm + normalA aq MnOEPA normalm …”
Section: Results and Discussionmentioning
confidence: 99%
“…In our previous work, we showed that such chemosensory nano-/ microspheres can be fabricated reliably with a high degree of repeatability, and their lifetime exceeds 2 months. 6 The microspheres selective for both anions (A) and cations (C) contained a chromoionophore (CH) as an optical transducer, which can be protonated/deprotonated in the presence of an ion exchanger (R). This change in the protonation degree of the chromoionophore is responsible for the change in the optical properties of the produced microspheres according to eqs 1 and 2 (for AS-MPs and CS-MPs, respectively).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations